Atezolizumab in the treatment of small cell lung cancer - Ordon, Kacper; Skonieczna, Karolina; Wiciun, Olimpia; Badziąg, Magdalena; Szulc, Paulina; Kurczoba, Laura; Kłossowska, Martyna; Kądziołka, Olga (Quality in Sport, 2025)
Small cell lung cancer (SCLC) remains one of the most aggressive cancers, with a high relapse rate and limited treatment outcomes. The introduction of immunotherapy, including PD-L1 inhibitors such as atezolizumab and durvalumab, has changed the standard of care, especially in advanced-stage disease (ES-SCLC). Combining immunotherapy with chemotherapy allows for prolonged survival and disease control, as confirmed in the IMpower133 and CASPIAN studies. New strategies, such as consolidation with lurbinectedin in the IMforte study, indicate further opportunities to improve treatment outcomes. In limited-stage disease (LS-SCLC), the groundbreaking results of the ADRIATIC study established immunotherapy with durvalumab as the standard of care after chemoradiotherapy. However, later lines of treatment and resistance to therapy remain a challenge, which is driving the development of new methods such as PARP inhibitors, anti-DLL3 antibodies, and adoptive immunotherapy. Advances in the molecular classification of SCLC and the identification of biomarkers pave the way for more precise and effective therapeutic approaches that may significantly improve patient prognosis in the future.